Efficient Quadrature Rules For Numerical Integration Based On Linear Legendre Multi-wavelets - Nur Neesha Alimin; Mohammad Hasan Abdul Sathar; Anvarjon A. Ahmedov; Muhammad Asyraf Asbullah; Ahmad Fadly Nurullah Rasedee (IOP Publishing Ltd, 2024)
In this work, generalize solution based on linear Legendre multi-wavelets are proposed for single, double and triple integrals with variable limits. To obtain the numerical approximations for integrals, an algorithm with the properties of linear Legendre multi-wavelets are applied. The main benefits of this method are its simple applicable and efficient. Furthermore, the error analysis for single, double and triple integrals is worked out to show the efficiency of the method. Numerical examples for the integrals are conducted by using linear Legendre multi-wavelets in order to validate the error estimation.